Profil keselamatan pasien dalam penggunaan irigasi hangat perioperatif: A literature review - Harlasgunawan, Alia Rahmi; Kosasih, Cecep Eli; Nur'aeni, Aan (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Perioperative hypothermia (core temperature < 36 °C) is a frequent complication during surgery and is associated with adverse outcomes such as myocardial ischemia, coagulopathy, surgical site infections, and delayed recovery. One of the contributing factors is the use of large volumes of room-temperature irrigation fluids. Warming irrigation fluids is a simple and effective strategy to maintain perioperative normothermia, but its implementation requires a thorough understanding of patient safety profiles to ensure safe and optimal practice. Purpose: To analyze the patient safety profile in the use of perioperative warm irrigation. Method: A literature review was conducted on relevant literature to analyze the effectiveness and safety profile of perioperative warmed irrigation fluids. The reviewed literature included clinical studies and research discussing the use of warmed irrigation fluids in various surgical procedures, focusing on hypothermia prevention, patient thermal comfort, and safety aspects. Data were analyzed descriptively to identify key findings regarding effectiveness, safety profile, and clinical practice recommendations. Results: Evidence from various clinical studies shows that warmed irrigation fluids improve thermal comfort, reduce the incidence of hypothermia and shivering, and support patient safety. The effectiveness is particularly notable in endoscopic and urologic procedures, and can be enhanced when combined with warmed intravenous fluids. However, the added value of combining multiple warming strategies in short-duration surgeries remains unclear. Importantly, the use of warmed irrigation fluids has not been linked to increased postoperative complications. Conclusion: Warmed irrigation fluids demonstrate an excellent safety profile when implemented optimally. Optimal implementation requires consistent temperature control, reliable warming equipment, and adherence to safety protocols. Further standardization of safety protocols and healthcare professional training in intraoperative fluid warming practices is needed to optimize patient safety outcomes and ensure safe implementation across various clinical settings. Keywords: Hypothermia; Patient Safety; Perioperative Warm Irrigation. Pendahuluan: Hipotermia perioperatif (suhu inti tubuh < 36 °C) merupakan komplikasi yang sering terjadi selama pembedahan dan berhubungan dengan berbagai efek merugikan, seperti iskemia miokard, gangguan koagulasi, infeksi luka operasi, serta pemulihan yang tertunda. Salah satu faktor yang berkontribusi adalah penggunaan cairan irigasi dalam volume besar dengan suhu ruang. Pemanasan cairan irigasi merupakan strategi yang sederhana dan efektif untuk mempertahankan normotermia selama perioperatif. Tujuan: Untuk menganalisis profil keselamatan pasien dalam penggunaan irigasi hangat perioperative. Metode: Tinjauan naratif dilakukan terhadap literatur yang relevan untuk menganalisis efektivitas dan profil keselamatan penggunaan cairan irigasi hangat perioperatif. Literatur yang dikaji mencakup studi klinis dan penelitian yang membahas penggunaan cairan irigasi hangat dalam berbagai prosedur pembedahan, dengan fokus pada pencegahan hipotermia, kenyamanan termal pasien, dan aspek keselamatan. Data dianalisis secara deskriptif untuk mengidentifikasi temuan utama terkait efektivitas, profil keselamatan, dan rekomendasi praktik klinis. Hasil: Bukti dari berbagai studi klinis menunjukkan bahwa cairan irigasi hangat meningkatkan kenyamanan termal, menurunkan kejadian hipotermia dan menggigil, serta mendukung keselamatan pasien. Efektivitasnya sangat menonjol pada prosedur endoskopi dan urologi, dan dapat ditingkatkan dengan kombinasi infus intravena hangat. Namun, manfaat tambahan dari penggabungan beberapa metode pemanasan pada pembedahan berdurasi pendek masih belum jelas. Penting untuk dicatat bahwa penggunaan cairan irigasi hangat tidak dikaitkan dengan peningkatan komplikasi pascaoperasi. Simpulan: Cairan irigasi hangat menunjukkan profil keselamatan yang sangat baik. Ketika diimplementasikan secara optimal membutuhkan kontrol suhu yang konsisten, peralatan pemanas yang andal, serta kepatuhan terhadap protokol. Standarisasi lebih lanjut dalam praktik pemanasan cairan intraoperatif diperlukan untuk mengoptimalkan luaran pasien. Kata Kunci: Hipotermia; Irigasi Hangat Perioperative; Keselamatan Pasien.